Environmental Modification and Anthropogenic Impacts on Urban Environment - Okiemute, Edewor Akpezi (Transpublika Publisher, 2025)
The paper focuses on environmental modification resulting from urban hazardous ecological impact induced by humans who are the most potent and fundamental agents of environmental alteration, exponential population growth, industrialization, poor sanitary conditions and general environmental depletion activities, thereby contributing to the decline of environmental quality. Thus, advancing mitigation and adaptation strategies to ameliorate environmental degradation. To provide an in- depth analysis of the subject matter, literature was reviewed while situating the research on a conceptual framework based on environmental possibilism, determinism and carrying capacity. Human activities which are the major ecological transformation agent in the urban area, can also be measured in terms of the biologically productive natural resources (land, water, air soils and the biologically active sphere). The study therefore recommends that social impact assessment, as well as environmental impact assessment, must be carried out to regulate man’s activities to mitigate environmental decline. These measures will safeguard, protect and conserve the environment and improve its quality to forestall indiscriminate damage.